Assessment of Nurses’ Knowledge toward Children with GuillainBarre Syndrome at Pediatric Hospitals in Baghdad City - Kudhaer, Weaam; Mua’ala, Eqbal (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: The study aimed to assess the level of pediatric nurses’ knowledge toward children with Guillain-Barre syndrome (GBS) and to find out the relationships between nurses’ knowledge and their demographic data. Methodology: A purposive “non probability” sample of (30) nurses was selected from medical neurological wards and Respiratory Care Units of Children Welfare Pediatric Teaching Hospital, Child’s Center Pediatric Teaching Hospital, AL-Kadhemia Teaching Hospital, Baghdad Teaching Hospital, and Neurological Science Hospital which has started from March 5 th 2009 to April 30th 2009. The study instrument consists of two parts. The first part is concerned with nurses’ demographical characteristic and the second one is concerned with nurses’ knowledge which is divided into two sections. Section one consists of (20) items which are related to nurses’ knowledge about general information of Guillain-Barre Syndrome, and section two (12) items concerning nurses’ knowledge in relation to nursing care of GBS. Data were collected through a special constructed questionnaire format which includes multiple choice questions. A selfadministration method was used. Data were analyzed by using SPSS packed version (10.0), a descriptive statistical analysis (frequencies, percentage, quartile, and mean of scores), and inferential statistical analysis (chi-square) were used.